Development of an E. coli strain for one-pot biofuel production from ionic liquid pretreated cellulose and switchgrass. Issue 15 (10th May 2016) - Frederix, Marijke; Mingardon, Florence; Hu, Matthew; Sun, Ning; Pray, Todd; Singh, Seema; Simmons, Blake A.; Keasling, Jay D.; Mukhopadhyay, Aindrila
Abstract : Integrating an ionic liquid tolerant E. coli strain with an ionic liquid tolerant cellulase for bioconversion of pretreated hydrolysate and cellulose to a bio jet-fuel precursor. Abstract : Biological production of chemicals and fuels using microbial transformation of sustainable carbon sources, such as pretreated and saccharified plant biomass, is a multi-step process. Typically, each segment of the workflow is optimized separately, often generating conditions that may not be suitable for integration or consolidation with the upstream or downstream steps. While significant effort has gone into developing solutions to incompatibilities at discrete steps, very few studies report the consolidation of the multi-step workflow into a single pot reactor system. Here we demonstrate a one-pot biofuel production process that uses the ionic liquid 1-ethyl-3-methylimidazolium acetate ([C2 C1 Im][OAc]) for pretreatment of switchgrass biomass. [C2 C1 Im][OAc] is highly effective in deconstructing lignocellulose, but nonetheless leaves behind residual reagents that are toxic to standard saccharification enzymes and the microbial production host. We report the discovery of an [C2 C1 Im]-tolerant E. coli strain, where [C2 C1 Im] tolerance is bestowed by a P7Q mutation in the transcriptional regulator encoded by rcdA . We establish that the causal impact of this mutation is the derepression of a hitherto uncharacterized major facilitator family transporter, YbjJ. To develop the strain for a one-pot process we engineered this [C2 C1 Im]-tolerant strain to express a recently reportedd -limonene production pathway. We also screened previously reported [C2 C1 Im]-tolerant cellulases to select one that would function with the range of E. coli cultivation conditions and expressed it in the [C2 C1 Im]-tolerant E. coli strain so as to secrete this [C2 C1 Im]-tolerant cellulase. The final strain digests pretreated biomass, and uses the liberated sugars to produce the bio-jet fuel candidate precursord -limonene in a one-pot process.